2022
DOI: 10.4041/kjod21.283
|View full text |Cite
|
Sign up to set email alerts
|

Variation in adhesion of Streptococcus mutans and Porphyromonas gingivalis in saliva-derived biofilms on raw materials of orthodontic brackets

Abstract: Objective: To evaluate differences in the adhesion levels of the most common oral pathogens, Streptococcus mutans and Porphyromonas gingivalis, in human saliva-derived microcosm biofilms with respect to time and raw materials of orthodontic brackets. Methods: The samples were classified into three groups of bracket materials: 1) monocrystalline alumina ceramic (CR), 2) stainless steel metal (SS), and 3) polycarbonate plastic (PL), and a hydroxyapatite (HA) group was used to mimic the enamel surface. Saliva was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
5
0
2
Order By: Relevance
“…2000). Si la persona no realiza el control químico y mecánico de esta placa para removerla constantemente, se formará el tártaro o cálculo dental que es precursor para el desarrollo de enfermedades buco dentales prevalentes en el país como la caries y los procesos periodontales como la gingivitis y periodontitis (;Poyato et al, 2001;Caufield et al, 2003).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…2000). Si la persona no realiza el control químico y mecánico de esta placa para removerla constantemente, se formará el tártaro o cálculo dental que es precursor para el desarrollo de enfermedades buco dentales prevalentes en el país como la caries y los procesos periodontales como la gingivitis y periodontitis (;Poyato et al, 2001;Caufield et al, 2003).…”
Section: Resultsunclassified
“…La desmineralización del esmalte sólo se produce cuando los ácidos bacterianos (responsables de la caída de pH disuelven la hidroxiapatita aun pH igual o inferior a 5,0, este pH tan bajo es consecuencia de la producción de ácido láctico en un 50%, ácido acético y fórmico, estos ácidos son liberados por las bacterias al fermentar los hidratos de carbono de la dieta (Leite et al, 2000;Kidd y Fejerskov, 2004;Newbrum, 2004;Kidd y Fejerskov, 2013;Fejerskov y Bente, 2017;Park et al, 2022).…”
Section: Resultsunclassified
“…Nevertheless, recent studies employing bracket materials and multispecies biofilms have aimed to determine which brackets are more susceptible to enamel demineralization. 19,46 These limited studies have indicated that bracket materials with rougher surfaces and higher surface-free energy tend to increase biofilm formation and the proportion of MS in the biofilm (Figure 4D-4F). 19,46 This is attributed to rougher surfaces providing an increased area for bacterial adhesion and protection of biofilms from shear forces, while higher surface-free energy thermodynamically facilitates bacterial adhesion and biofilm formation.…”
Section: Orthodontic Brackets and Enamel Demineralizationmentioning
confidence: 99%
“…Instead, the proportion of facultative bacteria, such as MS, may increase over time. [17][18][19] While biofilms develop through complex interactions among various strains, most orthodontic microbial studies investigating bacterial interactions with orthodontic appliances have used single species, predominantly S. mutans. [7][8][9][10][11][12]24 Moreover, saliva has been rarely included in orthodontic microbial research.…”
Section: Biofilm Formation Around Orthodontic Appliancesmentioning
confidence: 99%
See 1 more Smart Citation